2018
DOI: 10.1108/ssmt-10-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mn nanoparticle addition on wettability, microstructure and microhardness of low-Ag Sn-0.3Ag-0.7Cu-xMn(np) composite solders

Abstract: Purpose The purpose of this paper is to investigate of the effects of Mn nanoparticle addition on the wettability, microstructure and microhardness of SAC0307-xMn(np) (SAC: Sn–Ag–Cu; x = 0, 0.02, 0.05, 0.1 and 0.3 Wt.%) composite solders. Design/methodology/approach The SAC0307-xMn(np) composite solders were prepared by mechanically mixing different weight percentages of Mn nanopowders into the SAC0307 solder paste with rosin flux. In this study, the wettability of the solders was studied using contact angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thus, these reinforcing nanoparticles can enhance the quality and reliability properties of solder joints for ultra-fine package assembly.Due to the moderate price and the non-toxicity, the manganese is considered as an ideal dopant for the SAC solder alloys. Mn reported to have a grain refinement effect on the SAC solder alloys both in nanoparticle [9] and in micralloyed [10] form. At soldering temperature and below that the solubility of Mn in the Sn base solder alloy is relatively low; so even at very low concentration, Mn containing micro precipitation might appear inside the solder bulk which may act as a crystallization centre for the solidification of the SAC alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these reinforcing nanoparticles can enhance the quality and reliability properties of solder joints for ultra-fine package assembly.Due to the moderate price and the non-toxicity, the manganese is considered as an ideal dopant for the SAC solder alloys. Mn reported to have a grain refinement effect on the SAC solder alloys both in nanoparticle [9] and in micralloyed [10] form. At soldering temperature and below that the solubility of Mn in the Sn base solder alloy is relatively low; so even at very low concentration, Mn containing micro precipitation might appear inside the solder bulk which may act as a crystallization centre for the solidification of the SAC alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the reasonable price and harmless nature, manganese can be an optimal alloying element for the SAC solder alloys. Mn reportedly refines the grain structure in the SAC solder alloys when added either in the nanoparticle [ 22 ] or in the alloyed form [ 23 ]. Both at soldering temperature and below that, the solubility of Mn in the Sn solder alloy is low.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al measured the elongation and Young’s modulus of SAC solders alloyed with manganese and titanium [ 23 ] and showed an increase in the elongation and a decrease in the Young’s modulus. Manganese was also utilized in nanoparticle form [ 22 ]. Tang et al found that the optimal weight percentage of manganese nanoparticles is 0.05 wt.% to enhance the wettability of SAC alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Composite lead-free solders containing micro-, and nanoparticles have been extensively studied [1][2][3][4][5]. Due to grain-boundary resistance, these particles can inhibit the coarsening of the brazing material organization, especially the Cu 6 Sn 5 , Ag3Sn intermetallic compounds and β-Sn phases.…”
mentioning
confidence: 99%
“…The addition of a small amount of Bi to Sn-1.5Ag-0.7Cu solders reduces supercooling, refines the microstructure, reduces the nucleation rate of intermetallic compounds (IMCs), and improves creep resistance and fracture life solders. Cheng et al reported that the addition of low levels of Ni to Sn-1.0Ag-0.5Cu solders enhanced the growth of Cu 6 Sn 5 IMCs and inhibited the growth of Cu3Sn IMCs during solid-state aging [4]. Presently, two widely employed methods for fabricating composite solders with added reinforcement materials are the mechanical blending method and the powder metallurgy method.…”
mentioning
confidence: 99%